Fallopia Japonica and Prunella vulgaris inhibit myopia progression by suppressing AKT and NFκB mediated inflammatory reactions - Chih-Sheng Chen; Yu-An Hsu; Chia-Hung Lin; Yao-Chien Wang; En-Shyh Lin; Ching-Yao Chang; Jamie Jiin-Yi Chen; Ming-Yen Wu; Hui-Ju Lin; Lei Wan (BMC, 2022)
Abstract Background The increased global incidence of myopia requires the establishment of therapeutic approaches. This study aimed to investigate the effect of Fallopia Japonica (FJ) and Prunella vulgaris (PV) extract on myopia caused by monocular form deprivation (MFD). Methods We used human retinal pigment epithelial cell to study the molecular mechanisms on how FJ extract (FJE) and PV extract (PVE) lowering the inflammation of the eye. The effect of FJE and PVE in MFD induced hamster model and explore the role of inflammation cytokines in myopia. Results FJE + PVE reduced IL-6, IL-8, and TNF-α expression in RPE cells. Furthermore, FJE and PVE inhibited inflammation by attenuating the phosphorylation of protein kinase B (AKT), and nuclear factor kappa-light-chain-enhancer of activated B (NF-κB) pathway. In addition, we report two resveratrol + ursolic acid compounds from FJ and PV and their inhibitory activities against IL-6, IL-8, and TNF-α expression levels in RPE cells treated with IL-6 and TNF-α. FJE, PVE, and FJE + PVE were applied to MFD hamsters and their axial length was measured after 21 days. The axial length showed statistically significant differences between phosphate-buffered saline- and FJE-, PVE-, and FJE + PVE-treated MFD eyes. FJE + PVE suppressed expressions of IL-6, IL-8, and TNF-α. They also inhibited myopia-related transforming growth factor-beta (TGF)-β1, matrix metalloproteinase (MMP)-2, and NF-κB expression while increasing type I collagen expression. Conclusions Overall, these results suggest that FJE + PVE may have a therapeutic effect on myopia and be used as a potential treatment option.